Dermal mesenchymal stem cells (DMSCs) inhibit skin-homing CD8+ T cell activity, a determining factor of vitiligo patients' autologous melanocytes transplantation efficiency. - Miao-ni Zhou (PLoS ONE, 2013)
We here investigated the efficiency of autologous melanocyte transplantation of 23 vitiligo patients by focusing on perilesional skin homing CD8+ T lymphocytes, and studied the potential effect of dermal mesenchymal stem cells (DMSCs) on CD8+ T cell activities in vitro. Out of 23 patients with the autologous melanocyte transplantation, 12 patients (52.17%) had an excellent re-pigmentation, 6 patients (26.09%) had a good re-pigmentation, 5 patients (21.74%) had a fair or poor re-pigmentation. CD8+ T cells infiltrating was observed in the perilesional vitiligo area of all patients. Importantly, the efficiency of the transplantation was closely associated with skin-homing CD8+ T cell activities. The patients with high number of perilesional CD8+ T cells or high level of cytokines/chemokines were associated with poor re-pigmentation efficiency. For in-vitro experiments, we successfully isolated and characterized human DMSCs and skin-homing CD8+ T cells. We established DMSCs and CD8+ T cell co-culture system, where DMSCs possessed significant inhibitory effects against skin homing CD8+ T lymphocytes. DMSCs inhibited CD8+ T cells proliferation, induced them apoptosis and regulated their cytokines/chemokines production. Our results suggest that vitiligo patients' autologous melanocytes transplantation efficiency might be predicted by perilesional skin-homing CD8+ T cell activities, and DMSCs might be used as auxiliary agent to improve transplantation efficacy.